Working experiences of airport employees after a terrorist attack in Belgium: A qualitative study. (October 2021) - Van Overmeire, Roel; Vesentini, Lara; Van Keer, Rose-Lima; Muysewinkel, Emilie; Bilsen, Johan
Abstract: Terrorist attacks can cause loss of human lives, a possible mental health impact on those directly exposed, but also large economic and structural damage. However, few studies have looked into the work experience of those directly exposed returning to a workplace that was the target of terrorist attack. In this study, directly exposed employees of the March 22, 2016 airport bombing in Belgium were interview. Eighteen interviews were conducted with four women and fourteen male employees at Brussels Airport. Interviews were audio recorded, transcribed and analyzed using a reflexive thematic analysis. Four themes arose: unsafety at the workplace, fall-out of colleagues, distrust or support of colleagues, and a lack of trust in management. The need to reopen the airport clashed with the coping of the employees and resulted in a fall-out of employees throughout the years, distrust of management, and a general feeling of unsafety in the workplace. A lack of acknowledgment of the attacks and proper mental health aid offered to the employees seems to be at the basis of the problems indicated by the employees.